You are on page 1of 6

# Problem 10566. Proposed by Gerry Myerson, Macquarie University, Australia.

## Let S be a nite set of

cardinality n > 1. Let f be a real-valued function on the power set of S, and suppose that f(A B) =
min{f(A), f(B)} for all subsets A and B of S. Prove that

(1)
n|A|
f(A) = f(S) max f(A),
where the sum is taken over all subsets A of S and the maximum is taken over all proper subsets A of S.
Solution, by Omran Kouba (Higher Institute Of Applied Sciences And Technology, Damascus, Syria).
The following proposition is equivalent to the desired result.
Proposition: For any nite set S of cardinality n 1, and any function f : P(S) R satisfying
(A, B) P(S) P(S), f(A B) = min(f(A), f(B)) (1)
We have

AP

(S)
(1)
n|A|
f(A) = max(f(A) : A P

(S)),
where P

## (S) is the set of proper subsets of S.

We will prove this by induction on the cardinality n of S.
If n = 1 the desired equality is trivial. Assume the validity of the result for some n 1. Let S

be a
nite set of cardinality n + 1, and let f : P(S

## ) R be function satisfying (1). Choose an element S

,
and apply the recurrence hypothesis to the set S = S

## {} and to the functions

g :P(S) R : A f(A)
h :P(S) R : A f(A {})
(It is straightforward to see that h satisfy (1)). This implies the folowing two equalities

AP

(S)
(1)
n|A|
f(A) = max(f(A) : A P

(S))
def
=

AP

(S)
(1)
n|A|
f(A {}) = max(f(A {}) : A P

(S))
def
=
Noting that P

(S

## (S), {S} and {A {} : A P

(S)}, we conclude
that

AP

(S

)
(1)
n+1|A|
f(A) = f(S) + . (2)
Since A B A = A B we have, A B = f(A) f(B). This property prouves immediatly
that min(f(S), ). On the other hand, let A
0
be an element of P

## (S) such that = f(A

0
{}), we
have
f(A
0
) = f(S (A
0
{})) = min(f(S), f(A
0
{})) = min(f(S), )
We conclude that = min(f(S), ). It follows that
f(S) + =max(f(S), ) = max(f(S), , )
=max(f(A) : A P

(S

)).
This, combined with (2), prouves the result for n + 1 and completes the proof.
Published in AMM March 1999.
1
Problem 10601. Proposed by Wen-Xiu Ma, Universitat-GH Paderborn, Paderborn, Germany. Let n > 1
be an integer and let a
1
, a
2
, . . . , a
n
be complex numbers. Show that

1 a
1
a
2
1
a
2n1
1
1 a
2
a
2
2
a
2n1
2
.
.
.
.
.
.
.
.
.
1 a
n
a
2
n
a
2n1
n
0 1 2a
1
(2n 1)a
2n2
1
0 1 2a
2
(2n 1)a
2n2
2
.
.
.
.
.
.
.
.
.
0 1 2a
n
(2n 1)a
2n2
n

= (1)
n(n1)/2

1i<jn
(a
i
a
j
)
4
Solution, by Omran Kouba (Higher Institute for Applied Sciences And Technology, Damascus, Syria).
The aim is to calculate D(a
1
, . . . , a
n
) with
D(a
1
, . . . , a
n
) =

1 a
1
a
2
1
a
2n1
1
1 a
2
a
2
2
a
2n1
2
.
.
.
.
.
.
.
.
.
1 a
n
a
2
n
a
2n1
n
0 1 2a
1
(2n 1)a
2n2
1
0 1 2a
2
(2n 1)a
2n2
2
.
.
.
.
.
.
.
.
.
0 1 2a
n
(2n 1)a
2n2
n

,
we will assume that a
1
, a
2
, . . . , a
n
are distinct complex numbers, otherwise this determinant is zero. Let us
consider
Q(X) =

1 a
1
a
2
1
a
2n1
1
1 a
2
a
2
2
a
2n1
2
.
.
.
.
.
.
.
.
.
1 a
n
a
2
n
a
2n1
n
0 1 2a
1
(2n 1)a
2n2
1
0 1 2a
2
(2n 1)a
2n2
2
.
.
.
.
.
.
.
.
.
1 X X
2
X
2n1

## That is the determinant obtained from D(a

1
, . . . , a
n
) by replacing the last row by [1, X, X
2
, . . . , X
2n1
] so
that Q

(a
n
) = D(a
1
, . . . , a
n
). Clearly Q is a polynomial of degree at most 2n 1 and that Q(a
k
) = 0 for
1 k n, Q

(a
k
) = 0 for 1 k n 1. This implies that Q(X) = (X a
n
)
n1

k=1
(X a
k
)
2
, where is the
coecient of X
2n1
in Q(X) that is
=

1 a
1
a
2
1
a
2n2
1
1 a
2
a
2
2
a
2n2
2
.
.
.
.
.
.
.
.
.
1 a
n
a
2
n
a
2n2
n
0 1 2a
1
(2n 2)a
2n3
1
0 1 2a
2
(2n 2)a
2n3
2
.
.
.
.
.
.
.
.
.
0 1 2a
n1
(2n 2)a
2n3
n1

.
1
Again we consider
P(X) =

1 a
1
a
2
1
a
2n2
1
1 a
2
a
2
2
a
2n2
2
.
.
.
.
.
.
.
.
.
1 X X
2
X
2n2
0 1 2a
1
(2n 2)a
2n3
1
0 1 2a
2
(2n 2)a
2n3
2
.
.
.
.
.
.
.
.
.
0 1 2a
n1
(2n 2)a
2n3
n1

Clearly = P(a
n
). But P is polynomial of degree at most 2n 2 such that P(a
k
) = P

(a
k
) = 0
for k = 1, . . . , n 1 and the coecient of X
2n2
is (1)
n1
D(a
1
, . . . , a
n1
). This shows that P(X) =
(1)
n1
D(a
1
, . . . , a
n1
)
n1

k=1
(X a
k
)
2
, and
= (1)
n1
D(a
1
, . . . , a
n1
)
n1

k=1
(a
n
a
k
)
2
Noting that Q

(a
n
) =
n1

k=1
(a
n
a
k
)
2
and replacing the value of we obtain
D(a
1
, . . . , a
n
) = (1)
n1
(
n1

k=1
(a
n
a
k
)
4
)
D(a
1
, . . . , a
n1
).
A simple induction proves then that
D(a
1
, . . . , a
n
) = (1)
n(n1)/2

1i<jn
(a
i
a
j
)
4
Published in AMM August-September 1999
2
Problem 10621. Proposed by Harold G. Diamond and Bruce Reznick, University of Illinois, Urbana-
Champain, IL. Let F(x) denote the Cantor singular function, that is, the unique non-decreasing function on
[0,1] such that, if x =

j=1
2
j
/3
j
with {0, 1} then F(x) =

j=1

j
/3
j
. It is clear by symmetry that

1
0
F(x)dx = 1/2. Prove that

1
0
(F(x))
2
dx =
3
10
and

1
0
(F(x))
3
dx =
1
5
.
More generally, evaluate

1
0
(F(x))
n
dx for every positive integer n.
Solution, by Omran Kouba (Higher Institute for Applied Sciences And Technology, Damascus, Syria).
The aim of this problem is to evaluate

1
0
(F(x))
n
dx, where F is the Cantors singular function, and n any
positive integer.
Noting that F is the unique non decreasing function on [0, 1] such that F(

j=1
2
j
/3
j
) =

j=1

j
/2
j
for every
sequence (
j
)
j1
from {0, 1}, one can easily prove the following self-similarity property:
Proposition: For every x [0, 1], we have
F(x) = 2F(
x
3
) = 2F(
2
3
+
x
3
) 1.
Let us now dene A(t) =

1
0
exp(tF(x)) dx for t R. Using the above mentioned self-similarity property
and the fact that F(1/3) = F(2/3) = 1/2, we can see that
A(2t) =

1/3
0
exp(2tF(x)) dx +

2/3
1/3
exp(2tF(x)) dx +

1
2/3
exp(2tF(x)) dx
=
1
3

1
0
exp(2tF(x/3)) dx +
1
3
e
t
+
1
3

1
0
exp(2tF(
2
3
+
x
3
)) dx
=
1
3
(A(t) +e
t
+e
t
A(t)).
This proves the following functional equation
1 + 3A(2t) (1 +e
t
)(1 +A(t)) = 0 ()
On the other hand, letting J
n
=

1
0
(F(x))
n
dx, we have A(z) =

n=0
z
n
n!
J
n
.
Replacing back into (), we conclude that

n=0
(
(3 2
n
1)J
n
1
n

k=0
(
n
k
)
J
k
)
t
n
n!
= 0
This allows us to evaluate the sequence (J
n
)
n0
by the following induction:
J
0
= 1, J
1
=
1
2
, J
n
=
1
3 2
n
2
(
2 +
n1

k=1
(
n
k
)
J
k
)
, for n 2.
Finally, here are some values
J
2
=
3
10
, J
3
=
1
5
, J
4
=
33
230
, J
5
=
5
46
, J
6
=
75
874
My solution was published in AMM February 1999 page 175.
1
Problem 10624. Proposed by William F.Trench, Trinity University, San Antonio TX. Suppose that
a
0
> a
1
> a
2
> and lim
n
a
n
= 0. Dene S
n
=

j=n
(1)
jn
a
j
= a
n
a
n+1
+a
n+2
. Show that

a
n
S
n
< if and only if

a
2
n
< .
Solution, by Omran Kouba (Higher Institute Of Applied Sciences And Technology, Damascus, Syria).
Lemma: Let (a
n
)
n0
and (b
n
)
n0
be two sequences of non negative real numbers such that
n 0, b
n
a
n
b
n
+b
n+1
()
Then the following are equivalent: i:

a
2
n
< , ii:

a
n
b
n
< and iii:

b
2
n
< .
In fact, mutiplying the members of () by b
n
and summing we conclude that, for every natural number m,
we have
m

n=0
b
2
n

m

n=0
a
n
b
n

m

n=0
b
2
n
+
m

n=0
b
n
b
n+1

n=0
b
2
n
+
(
m

n=0
b
2
n
)
1/2
(
m+1

n=1
b
2
n
)
1/2

m+1

n=0
b
2
n
+
(
m+1

n=0
b
2
n
)
1/2
(
m+1

n=0
b
2
n
)
1/2
= 2
m+1

n=0
b
2
n
.
where we used the Cauchy-Schwarz inequality. This proves that ii iii.
On the other hand, by squaring () and proceding as before we get
m

n=0
b
2
n

m

n=0
a
2
n

m

n=0
b
2
n
+
m+1

n=1
b
2
n
+ 2
m

n=0
b
n
b
n+1
2
m+1

n=0
b
2
n
+ 2
(
m

n=0
b
2
n
)
1/2
(
m+1

n=1
b
2
n
)
1/2
4
m+1

n=0
b
2
n
.
This proves that i iii.
The statment of the problem follows by noting that (a
n
)
n0
and (S
n
)
n0
are two sequences of non negative
real numbers such that n 0, S
n
a
n
= S
n
+S
n+1
, which is easy to verify.
Published in AMM March 1999.
1
Problem 10625. Proposed by Olaf Kraft, and Martin SChaefer, Technical University Aachen, Aachen
Germany. For x > 0 and n N, dene
a
n
=

2
n1
i=0
(
2
n
2i
)
x
i

2
n1
1
i=0
(
2
n
2i+1
)
x
i
.
Evaluate lim
n
a
n
.
Solution, by Omran Kouba (Higher Institute Of Applied Sciences And Technology, Damascus, Syria).
We will prove the more general result:
Lemma: For x > 0, let (b
n
)
n1
be dened by
b
n
=

0in/2
(
n
2i
)
x
i

0i<n/2
(
n
2i + 1
)
x
i
Then lim
n
b
n
=

x
It follows that a
n
= b
2
n converges to

x and answers the question of the problem.
To prove the lemma note that
b
n

x
b
n
+

x
=
n

i=0
(
n
i
)
(1)
i
(

x)
i
n

i=0
(
n
i
)
(

x)
i
=
(
1

x
1 +

x
)
n
=
n
.
Since =
1

x
1 +

x
= 1
2

x
1 +

x
= 1 +
2
1 +

x
, we conclude that (1, 1) and lim
n

n
= 0. Finally,
b
n
=
1 +
n
1
n

x, so that lim
n
b
n
=

x.
Published in AMM May 1999.
1